Analysis Of The Efficiency Of Sharia-Based Banks On Customer Interest In Indonesian - Safi’atus Sholikhah; Putri Ayu Andesia; Zufaruddin Zaidan; Maida Nurul Adila (Bulletin of Islamic Economics, 2025)
This study analyzes the operational efficiency of Islamic banks in Indonesia using the Data Envelopment Analysis (DEA) method with an input-oriented approach. DEA is applied to evaluated how Islamic banks optimally utilize their resources in producing outputs. The input variables used include operating costs, total assets, and total labor, while the outputs include third-party funds (DPK), financing disbursed, and net income. The results show that there are variations in efficiency among banks, where some banks have achieved optimal efficiency, while others need improvement in resource management. This research provides strategic insights to improve the efficiency of Islamic banks at the regional level.